Foseco non-ferrous foundryman's handbook - Brown, John R. (Oxford [England] ; Boston : Butterworth-Heinemann, 1999)
The Non-Ferrous Foundryman's Handbook provides a practical reference book for all those concerned with dealing with aluminium, copper and magnesium casting alloys. International SI units are used throughout, but in almost all cases conversions to the more familiar Metric and Imperial units are given. Wherever possible, Casting Alloy Specifications include equivalent specifications for several countries as well as international specifications. Individual chapters cover the casting of all types of non-ferrous metals. For each group of alloys, specifications, and typical applications are describe.
Tables and general data -- Aluminium casting alloys -- Melting aluminium alloys -- Fluxes -- INSURAL refractory for ladles and metal transport -- Treatment of aluminium alloy melts -- Running, gating and feeding aluminium castings -- Filtration of aluminium alloy castings -- Pressure diecasting of aluminium alloys -- Low pressure and gravity diecasting -- Sand casting processes -- Sands and sand bonding systems -- Resin bonded sand -- Sodium silicate bonded sand -- Magnesium casting -- Copper and copper alloy castings -- Feeding systems.
Prev. eds. published under title: Foseco foundryman's handbook.
Includes index.
Keywords: Founding -- Handbooks, manuals, etc; Nonferrous metals -- Founding -- Handbooks, manuals, etc; Electronic books; Handbooks, manuals, etc